1991
DOI: 10.3109/01485019108987636
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase, Sperm ATP Concentrations, and Epididymal Function

Abstract: It has been suggested that a-glucosidase may be a marker of epididymal patency and function. Spermatozoal ATP concentrations decrease during passage through the epididymis, indicating efficient maturation. We correlated sperm motility with seminal plasma a-glucosidase activity and spermatozoal ATP. The sperm motility correlation with a-glucosidase activity was significantly positive, and the sperm motility correlation with spermatozoal ATP was significantly negative. It appears that high-aglucosidase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 7 publications
3
7
0
Order By: Relevance
“…This correlation is in agreement with Tremblay et al. (1979) and Fourie et al. (1991) who found that seminal plasma α ‐1,4‐glucosidase‐specific activity of semen correlated with sperm motility and that an abnormal function of the epididymis might be expected with a decreased production of this enzyme.…”
Section: Discussionsupporting
confidence: 91%
“…This correlation is in agreement with Tremblay et al. (1979) and Fourie et al. (1991) who found that seminal plasma α ‐1,4‐glucosidase‐specific activity of semen correlated with sperm motility and that an abnormal function of the epididymis might be expected with a decreased production of this enzyme.…”
Section: Discussionsupporting
confidence: 91%
“…Functional competence is acquired during passage through the epididymal lumen [Dacheux et al 2003]. In a multiple regression analysis model, a positive significant association between NAG and percentage progressive motile spermatozoa was observed in this study, as reported by others [Fourie et al 1991;Viljoen et al 1990], indicating the importance of this organ for sperm maturation. The present study demonstrated decreased total activity of NAG among men over 50 years of age compared to younger men.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, the more the amount of sperm was, the higher the concentration of alpha-glucosidase in epididymis. There was a correlation between the level of alpha-glucosidase and sperm motility, especially significant correlation between the level of alpha-glucosidase and the sperm progressive motility [7][8][9]11]. However, our data showed that there was no any apparent correlation between the alpha-glucosidase activity in seminal plasma and total motile sperm or grades a and b motile sperm, similar to some other studies [11].…”
Section: Discussionsupporting
confidence: 87%